(untitled) (Proceedings OPTIMAL, 2024)
Stunting in children under five is a major nutritional problem in Indonesia. Malnutrition in toddlers is caused by the nutritional content of the food consumed being unbalanced so that nutritional adequacy levels are not met. Generally, the food consumed by toddlers is influenced by the mother’s understanding of their eating patterns. This study aims to determine the relationship between maternal knowledge about feeding and the incidence of stunting among toddlers in the working area of the Alue Bilie Community Health Center, Darul Makmur District, Nagan Raya Regency. The type of research used is analytical with a cross-sectional study. The population is all mothers who have toddlers with malnutrition in the working area of the Alue Bilie Community Health Center, Darul Makmur District, Nagan Raya Regency. The sampling technique was stratified proportional random sampling so that the number of respondents was 33 people. Data analysis used the Chi-Square test. The research results show a relationship between maternal knowledge about feeding and the incidence of stunting among toddlers in the working area of the Alue Bilie Health Center, Darul Makmur District, Nagan Raya Regency, with a p-value of 0.018. It is hoped that the results of this research can be used as input information in formulating health program policies and strategies, especially those related to increasing mother knowledge about feeding toddlers as an effort to increase mother knowledge about feeding toddlers in preventing stunting.